Sistem Evaluasi Pada Aplikasi Akademik Menggunakan Metode Skala Likert Dan Algoritma Naïve Bayes - Erinsyah, Moh. Fiqih; Sasmito, Ginanjar Wiro; Wibowo, Dega Surono; Bakti, Very Kurnia (Program Studi Teknik Informatika - Universitas Komputer Indonesia (UNIKOM), 2024)
Harapan Bersama Polytechnic, Tegal City (Harber Polytechnic), is one of the higher education institutions. At the Harber Polytechnic there are various fields in carrying out the listed sections, one of which is the Information and Communication Technology (ICT) field. An agency must have a system that is used to facilitate and carry out its goals. An academic system or application used by agencies, namely Oase and Syncnau. From the existence of this system, of course, a place or place is needed to listen to it, to find out how satisfied the users are who often use the system, which is realized in the form of a web repository and evaluation. The web repository is used to store the academic system data and evaluation results using two methods, namely the Likert Scale Method and the Naïve Bayes Algorithm. Of the two methods used as a choice of questionnaires and text mining from user reviews who have filled out the questionnaire. The Likert scale method used uses four Likert levels, namely strongly agree, agree, disagree and strongly disagree. whereas for text mining it was made using the Naïve Bayes algorithm from the results of the build model to get a fairly high percentage quality level of 83.6%, and the test results of the model were also quite satisfactory so that the use of text mining is useful in opening an institution's academic system. These results have been analyzed by this method and the final result of the evaluation is the percentage level of system satisfaction and the results of comments or reviews that have been classified to make it easier for developers to develop academic systems in the future.